2003
DOI: 10.1538/expanim.52.401
|View full text |Cite
|
Sign up to set email alerts
|

The Rat Model of Type 2 Diabetic Mellitus and Its Glycometabolism Characters

Abstract: Abstract:To develop a rat model of type 2 diabetic mellitus that simulated the common manifestation of the metabolic abnormalities and resembled the natural history of a certain type 2 diabetes in human population, male Sprague-Dawley rats (4 months old) were injected with low-dose (15 mg/kg) STZ after high fat diet (30% of calories as fat) for two months (L-STZ/2HF). The functional and histochemical changes in the pancreatic islets were examined. Insulin-glucose tolerance test, islet immunohistochemistry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
80
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 16 publications
13
80
1
3
Order By: Relevance
“…The animals were successively intragastric administration with fat milk for 20 days and abdominal cavity injection with streptozotocin (STZ) 45 mg/kg. After fasting 72 h, those with the blood glucose over 11 mmol/L were taken as successful modeling and involved in the T2D group [27,28]. Sample preparation was carried out in 'Section 2.3' and a 5 L aliquot of the reconstructed solution was injected into the UPLC-Q-TOF/MS system.…”
Section: Metabolic Profiling Analysis Of T2d Rat Livermentioning
confidence: 99%
“…The animals were successively intragastric administration with fat milk for 20 days and abdominal cavity injection with streptozotocin (STZ) 45 mg/kg. After fasting 72 h, those with the blood glucose over 11 mmol/L were taken as successful modeling and involved in the T2D group [27,28]. Sample preparation was carried out in 'Section 2.3' and a 5 L aliquot of the reconstructed solution was injected into the UPLC-Q-TOF/MS system.…”
Section: Metabolic Profiling Analysis Of T2d Rat Livermentioning
confidence: 99%
“…Type 2 diabetes is characterized by reduced insulin sensitivity (insulin resistance) and higher blood glucose. In the present experiment, insulin resistance was induced by a high-fat diet initially (11). Thereafter, a low-dose STZ injection slightly reduced the number of β cells, which eventually resulted in hyperglycemia (12).…”
Section: Discussionmentioning
confidence: 57%
“…In the present study, the pathophysiological conditions of human type II DM was demonstrated in experimental animals by feeding them with a HCD for two months followed by an intraperitoneal injection of mild dose of STZ following the procedures described elsewhere (Wang et al, 2007;Zhang et al, 2003). From the preliminary physiological and biochemical observations, it was obvious that we succeeded in establishing the typical characteristics of human type II DM in experimental rats.…”
Section: Discussionmentioning
confidence: 69%
“…All rats could eat and drink ad libitum. After two months of HCD feeding, streptozotocin (STZ) at a dose of 15 mg/ kg body weight (Zhang et al, 2003) in 0.1 M citrate buffer (pH 4.6) was injected intraperitoneally. Seventytwo hours after STZ injection, the fasting blood glucose levels were measured and animals having blood glucose values greater than 300 mg/dL were selected for further experimentation.…”
Section: Preparation Of Extractsmentioning
confidence: 99%